Carer Appraisal Scale: A Pilot Study of a Novel Carer-Based Assessment of Patient Functioning. (March 2018) - Jeyasingam, Neil
Measurement of patient outcomes is an integral part of mental health service evaluation, as well as guiding clinical practice to ensure best outcomes for patients. Moreover, carers have long held a need for a voice in care outcomes. Despite there existing numerous tools for quantifying patient functioning based on clinician assessments or self-reports, there is a serious paucity of tools available for the carers of patients to appraise their functioning. This tool, developed for use in a community aged care psychiatric service, involves 4 sections—a global impression of patient progress, a scorable checklist of patient functioning in multiple domains, a qualitative section for identifying the most pressing concerns from the carer's perspective, and an open-ended feedback on treatment to date. In this pilot study, the Carer Appraisal Scale was found to have a fair correlation with the Health of Nation Outcomes Scale for over 65. This tool has potential for use in community aged care psychiatric services, as it provides a framework for communication of concerns, assists in prioritizing care, and adds value to clinician treatment plans, as well as providing another dimension to assessment of the patient while empowering carers in care participation. Practical implications of its use, limitations, and potential for modifications are also discussed.